A test of fundamental questions in mimicry theory using long‐term datasets. (27th June 2015) - Long, Elizabeth C.; Edwards, Kyle F.; Shapiro, Arthur M.
<x xml:space="preserve">Abstract</x> Since the phenomenon of mimicry was first described by Bates in 1862 it has become one of the foundational examples of adaptive evolution. Numerous subcategories of mimicry and dozens of hypotheses pertaining to its evolution and maintenance have been proposed. Many of these hypotheses, however, are difficult to test in experimental settings, and data from natural observations are often inadequate. Here we use data from a long‐term survey of butterfly presence and abundance to test several hypotheses pertaining to Batesian and female‐limited polymorphic mimicry (FPM; a special case of Batesian mimicry). We found strong evidence that models outnumber mimics in both mimicry systems, but no evidence for an increase in relative abundance of FPM mimics to their Batesian counterparts. Tests of the early‐emergence/model first hypothesis showed strong evidence that the Batesian mimic routinely emerges after the model, while emergence timing in the FPM system was site specific, suggesting that other ecological factors are at play. These results demonstrate the importance of long‐term field observations for testing evolutionary and ecological hypotheses.